Origins and Resolution of Financial Crises; Lessons from the Current and Northern European Crises - Finn Ostrup; Lars Oxelheim; Clas Wihlborg (Research Institute of Industrial Economics (IFN), 2009)
Since July 2007 the world economy has experienced a severe financial crisis originating in the U.S. housing market. The crisis has subsequently spread to the financial sectors in European and Asian economies and led to a severe worldwide recession. The existing literature on financial crises rarely distinguish between factors that create the original strain on the financial sector and factors that explain why these strains lead to system-wide contagion and a possible credit crunch. Most of the literature on financial crises refers to factors that cause an original disruption in the financial system. We argue that a financial crisis with its contagion within the system is caused by failures of legal, regulatory and political institutions. One policy implication of our view is that the need for various forms of rescues of financial firms in times of crises would be reduced if appropriate institutions could be put in place Lacking appropriate institutions to avoid contagion within the financial system and a potential credit crunch, ad hoc financial crisis management is required. We draw on experiences from the financial crises in the Nordic countries at the end of the 1980s and the beginning of the 1990s. In particular, the Swedish model for crisis resolution, which has received attention during the current crisis, is discussed in order to illustrate the problems policy makers face in a financial crisis without appropriate institutions. Current European Union approaches to the crisis are discussed before turning to policy implications from an emerging market perspective in the current crisis.
Keywords: D53; E44; E58; F32; F42; F55; G15; G18; G21; G28; 330; Financial Crisis; Institutional Failure; Insolvency Procedures; Contagion; Systemic Effects; Macroeconomic Shock; Financial Crisis Management; Swedish Model; Finanzkrise; Internationaler Finanzmarkt; Bankenkrise; Schock; Institutionelle Infrastruktur; Geldpolitik; Regulierung; Internationale Wirtschaftspolitik; Europa; USA; Nordeuropa; Schweden